The economic problem: From barter to commodity money to electronic money - Jan Kriegel (Levy Economics Institute of Bard College, 2021)
The success of alternative payment systems has led to discussion of various proposals to replace money with a new technology-based system, though many lack a clear idea of what exactly is the "money" they seek to replace. We begin by presenting the explanation of money's role in the economy embraced by most mainstream economists and policy analysts, based on the idea that money evolved out of the process of market exchange. An alternative explanation that looks on money as a part of the organization of production and distribution based on network clearing systems across balance sheets expressed in a common unit of account is then presented, distinguishing between a purely notional unit of account and means of settlement or discharge of debt. The final section addresses the possibility of a fundamentally different modern extension of this alternative approach that is not inspired by digital technology, distributed ledger accounting, or application operating on a mobile/cell phone system, but rather the actually existing system available from an internet telephone service provider that currently offers subsidiary domestic and international payment services whose operating procedures come close to replicating the alternative explanation of money mentioned above, with the potential to provide all the services of the existing payments system at lower costs and greater stability.
Keywords: B5; E42; E50; G2; 330; Banking Principle; Clearing Union; Imaginary Money; Money; Payment Systems; Unit of Account; Webtel.mobi